PENDIDIKAN MULTIKULTURAL SEBAGAI PEMBENTUKAN KARAKTER PESERTA DIDIK - Muhammad Anas Ma`arif (TA'LIM : Jurnal Studi Pendidikan Islam, 2019)
The realization of multicultural education is not just students getting material at school, but students also need to be able to experience multicultural practice firsthand. Thus, teachers, principals, school staff, employees, and security guards must be able to create a multicultural atmosphere in the school environment. And, multicultural education should not only be obtained in formal education, but non-formal education and informal education must also implement a multicultural system. this study uses library research in which data is taken from books, journals, which are relevant to the theme. This research resulted in the internalization of multicultural education on integral aspects in the subjects of students. The value internalized must contain elements of tolerance and mutual insult so that people can respect one another